Model pembelajaran Nahwu berbasis PAIKEM (Pembelajaran, Aktif, Inovatif, Kreatif, Efektif, & Menyenangkan) - Abdulloh, Muhammad; Sa'diyah, Maemunah; Ibdalsyah (TAWAZUN: Jurnal Pendidikan Islam, 2024)
The purpose of writing is to formulate a PAIKEM (active, creative, innovative, effective and fun learning)-based Nahwu learning model. Qualitative research method with field research type (Field Research) as research object at MA MQL BISA Bogor and MA Darul Muttaqien Parung. The results of the research found that the most significant obstacles consisted of internal factors of lack of motivation, student commitment and low self-confidence, external factors of inadequate learning media, ineffective Arabic language environment, and lack of supervision of recording student violations. In order to answer these obstacles, a PAIKEM-based Nahwu learning model was formulated with learning stages consisting of four stages, namely the experiencing stage, the interaction stage, the communication stage and the reflection stage. A social system consisting of building a positive learning atmosphere, determining class rules, practices to strengthen norms, integration with PAIKEM. Social principles consist of providing positive feedback, individualizing approaches, constructive criticism, encouraging a learning atmosphere, stimulating student participation, and strengthening a growth mindset. The support system consists of interactive learning facilities, interesting teaching materials, teaching aids, a supportive learning environment, and teacher training. The instructional impact consists of mastery of the concept of Nahwu, Arabic language skills, and the ability to analyze texts. And the accompanying impacts consist of critical thinking skills, collaboration skills, motivation for independent learning, use of technology, and cultural awareness. Abstrak Tujuan penulisan untuk merumuskan model pembelajaran Nahwu berbasis PAIKEM (pembelajaran aktif, kreatif, inovatif, efektif, dan menyenangkan). Metode penelitian kualitatif dengan tipe penelitian lapangan (Field Research) objek penelitian di MA MQL BISA Bogor dan MA Darul Muttaqien Parung. Hasil dari penelitian ditemukan bahwa hambatan yang paling signifikan terdiri dari faktor internal kurangnya motivasi, komitmen siswa dan rendahnya percaya diri, faktor eksternal media pembelajaran yang tidak memadai, tidak efektifnya lingkungan berbahasa Arab, dan kurangnya pengawasan pencatatan pelanggaran siswa. Guna menjawab hambatan tersebut dirumuskan model pembelajaran Nahwu berbasis PAIKEM dengan Tahapan pembelajaran yang terdiri dari empat tahap yaitu tahap mengalami, tahap interaksi, tahap komunikasi, dan tahap refleksi. Sistem sosial yang terdiri dari membangun suasana belajar yang positif, menentukan peraturan kelas, praktik untuk menguatkan norma, integrasi dengan PAIKEM. Prinsip sosial terdiri dari memberi umpan balik positif, pendekatan individualisasi, kritik konstruktif, mendorong suasana belajar, merangsang partisipasi siswa, dan menguatkan pola pikir pertumbuhan. Sistem pendukung terdiri dari sarana pembelajaran interaktif, bahan ajar yang menarik, alat peraga, lingkungan belajar yang mendukung, dan pelatihan guru. Dampak instruksional terdiri dari penguasaan konsep Nahwu, kemampuan berbahasa Arab, dan kemampuan menganalisis teks. Dan dampak pengiring terdiri dari kemampuan berpikir kritis, kemampuan kolaborasi, motivasi untuk belajar mandiri, penggunaan teknologi, dan kesadaran budaya.